Does monetary union reduce employment? - Anssi Rantala (Bank of Finland, 2001)
Bank of Finland Discussion Papers 7/2001 Anssi Rantala Does monetary union reduce employment? We use a two-country monetary model with unionized labor markets and open-economy spillovers to study the macroeconomic consequences of the formation of a monetary union.It is shown that the monetary regime affects the trade-off between real consumer wages and employment faced by the unions.Consequently, the equilibrium employment is endogenous and depends on the monetary regime.In particular, a switch from a floating exchange rate regime to a monetary union improves employment, provided that the degree of central bank conservatism is sufficiently high, whereas with low degrees of conservatism employment falls.Inflation is higher in a monetary union with all finite degrees of central bank conservatism.In addition, we consider an asymmetric fixed exchange rate regime as an alternative starting position for a monetary union.All results are derived assuming that labor unions are only interested in employment and real wages (not directly inflation) and that all structural parameters of the model remain unchanged when a monetary union is established.
URN:NBN:fi:bof-20140807234
Keywords: 330; monetary union; employment; labor unions; open-economy spillovers; central bank conservatism